Marginal Part-Time Employment in Indonesian Labor Market: Profile and Determinant - Dede Mahmuda (Jurnal Economia, 2020)
Abstract: The increase of marginal part-time employment has been found in developed countries, as well as in developing countries. This form of non-standard employment has very short work hours (less than 15 hours/week) and no guarantee of stable employment. In Indonesia, the share of part-time worker amongst working population increased from 15.4 percent in 2009 to 22.1 percent in 2018. Unfortunately, few studies discuss about marginal part-time employment. Using binary logistic regression, this study aims to identify marginal part-time workers based on their socio-demographic characteristic. The result indicates that female (OR: 1.81; 95% CI: 1.75-1.87), living in rural area (OR: 1.12; 95% CI: 1.08-1.16), and less educated are more likely to be marginal part-timer. Therefore, it is recommended for policymakers to ensure the labor regulation adequately protect the rights of part-time worker, so that the workers condition can be improved since they are most vulnerable group in the globalized economy.Keywords: non-standard employment, labor market, part-time, Indonesia Pekerja Paruh Waktu Marjinal Pada Pasar Tenaga Kerja Indonesia: Profil dan DeterminanAbstrak: Peningkatan pekerja paruh waktu marjinal telah teramati pada negara-negara maju dan juga negara berkembang. Salah satu bentuk pekerjaan non-standar ini memiliki jam kerja yang sangat pendek (kurang dari 15 jam seminggu) dan tidak adanya jaminan kestabilan pekerjaan. Di Indonesia, proporsi pekerja paruh waktu diantara penduduk bekerja meningkat dari 15,4 persen pada 2009 menjadi 22,1 persen pada 2018. Sayangnya, hanya sedikit studi yang membahas tentang pekerjaan paruh waktu marjinal. Dengan menggunakan regresi logistik biner, studi ini bertujuan untuk mengidentifikasi pekerja paruh waktu marjinal berdasarkan karakteristik sosio-demografinya. Hasil menunjukkan bahwa perempuan (OR: 1,81; 95% CI: 1,75-1,87), penduduk desa (OR: 1,12; 95% CI: 1,08-1,16), dan kurang berpendidikan berisiko lebih besar menjadi pekerja paruh waktu marjinal. Oleh karena itu, direkomendasikan bagi pembuat kebijakan untuk dapat memastikan peraturan ketenagakerjaan cukup untuk melindungi hak-hak pekerja paruh waktu khusus yang termarjinal agar kondisi pekerja dapat ditingkatkan karena mereka adalah kelompok paling rentan dalam ekonomi global.Kata kunci: pekerjaan non-standar, pasar tenaga kerja, paruh waktu, Indonesia